A book of five rings - Miyamoto, Musashi (Allison and Busby, 1974)
Written by legendary Japanese swordsman Musashi, this 17th-century exposition of sword-fighting strategy and Zen philosophy has been embraced by many contemporary readers, especially business school students, as a manual on how to succeed in life. There are many English translations, but every one, including this one, suffers from inadequate cultural, literary, and philosophical commentary. Musashi's work should be studied, not simply read, and Cleary's translation lacks commentary; it also makes the prose seems flat and the philosophy simplistic. Yet what makes this new translation worthwhile is the second text, buried deep in the back like an appendix: Yagyu Munenori's The Book of Family Traditions on the Art of War. This text, also an exposition on sword fighting and Zen philosophy, is difficult to find in an English translation, and its availability is welcome. Recommended for academic libraries generally